Development of Smart Gloves Prototype for Cyclists (Journal of Medical Device Technology, 2023)
Smart technologies have set their own standards and made their way into the current period. In that way, smart gloves have their own reputation for various purposes, such as gaming, boxing, power lifting, etc. However, there are not many smart gloves exclusively for cyclists in the market. Smart gloves for cyclists would be beneficial for monitoring their vitals during the athletic training or tracking their activity. There are few highly expensive wearable activity monitors that results in detecting the abnormal health status before it affects the athlete, during cycling and resistance exercise. In this paper, a smart glove prototype for cyclists is developed using Arduino software with affordable price, accurate reading of the heart rate, and oxygen-saturated level in the blood using MAX30100 sensor. The GPS enables locating and detecting the location of the user during the cycling activities. The determined data will be displayed on the Android smart phone of the user with the support of Bluetooth connection. The values can be monitored in real time, benefiting the user to act accordingly to the values in case of any significant abnormalities seen during the cycling activity. MIT app inventor had contributed a great part in accomplishing the mobile application for monitoring. As a result, in this study the developed prototype compensates the limitations of the existing smart glove and in cooperated it for serving its purpose at an affordable price.
Keywords: Smart cycling glove; Heart rate sensor; Arduino; Global Positioning System